Genetic divergence and phylogeography in the genus Nyctalus (Mammalia, Chiroptera): Implications for population history of the insular bat Nyctalus azoreum - salgueiro, P.; Ruedi, M.; Coelho, M.M.; Palmeirim, J.M. (Genetica, 2007)
We used three mitochondrial DNA fragments with different substitution rates (ND1, Cyt b and the CR) to infer phylogenetic relationships among six species of the genus Nyctalus, and compare levels of genetic divergence between the insular, vulnerable Nyctalus azoreum and its continental counterpart to assess the origins of the Azorean bat. The larger species found throughout the Palaearctic region (N. lasiopterus, N. aviator and N. noctula) share a unique chromosome formula (2n = 42) and form a monophyletic clade in our reconstructions. Nyctalus plancyi (= velutinus), a Chinese taxon with 2n = 36 chromosomes, is sometimes included in N. noctula, but is genetically very divergent from the latter and deserves full species status. All Cyt b and CR haplotypes of N. azoreum are closely related and only found in the Azores archipelago, but when compared to continental sequences of N. leisleri, levels of mtDNA divergence are unusually low for mammalian species. This contrasts with the high level of differentiation that N. azoreum has attained in its morphology, ecology, and echolocation calls, suggesting a recent split followed by fast evolutionary change. The molecular data suggest that N. azoreum originated from a European population of N. leisleri, and that the colonisation of the Azores occurred at the end of the Pleistocene. The Madeiran populations of N. leisleri also appear to have a European origin, whereas those of the Canary Islands probably came from North Africa. In spite of its recent origin and low genetic divergence, the Azorean bat is well differentiated and consequently represents a unique evolutionary unit with great conservation value.